Zwischen Sprachspiel und Methode. Perspektiven der Diskursanalyse - Feustel, Robert; Schochow , Maximilian (BEHEMOTH A Journal on Civilisation)

Finite Symplectic Matrix Groups - Kirschmer, Markus (Experimental Mathematics)
This paper classifies the maximal finite subgroups of SP₂ₙ(Q) for 1⩽n⩽11 up to GL₂ₙ(Q) conjugacy in .
Keywords: General Mathematics

Kommentar aus religionspädagogischer Sicht - Hymnologiedidaktische Überlegungen - Schroeter-Wittke, Harald (Singen im Gottesdienst. Ergebnisse und Deutungen einer empirischen Untersuchung in evangelischen Gemeinden)

Auf der Suche nach der Identität Europas - Kultur als transformatorische Kraft - Schroeter-Wittke, Harald (Perspektiven für ein Europa im Zeitalter der Globalisierung. 60 Jahre Evangelische Akademie Villigst / Iserlohn)

Den Schein wahren. Neun Responsorien auf das praktisch-theologische Interesse an den Oberflächen - Schroeter-Wittke, Harald (Lebenswissenschaft Praktische Theologie?)

Schaut hin! Rede für die Gedenkfeier am 2. April 2008 - Schroeter-Wittke, Harald (So fern und doch so nah... Wider das Vergessen)

Wewelsburg - Religionssensibilität an einem Ort des Schreckens - Schroeter-Wittke, Harald; Arnhold, Oliver (Religionssensible Schulkultur)

Hochkultur oder Popkultur? - Schroeter-Wittke, Harald; Marti, Andreas (Reformierte Liturgik - kontrovers)

Religionssensible Musik - Eine Klangreise - Schroeter-Wittke, Harald (Religionssensible Schulkultur)

Was ist Religionssensibilität? - Schroeter-Wittke, Harald (Religionssensible Schulkultur)

Intensity dependence of optically-induced injection currents in semiconductor quantum wells - Pochwala, Michal; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (CLEO:2011 - Laser Applications to Photonic Applications)
The intensity dependence of optically-induced injection currents in semiconductor quantum wells is investigated numerically. Oscillatory behavior of the electron charge current transients as function of intensity and time is predicted and explained.
Keywords: tet_topic_qw

Simulation of Mutual Coupling of Photonic Crystal Cavity Modes and Semiconductor Quantum Dots - Declair, S.; Song, X.; Meier, Torsten; Förstner, Jens (THE FOURTH INTERNATIONAL WORKSHOP 2011)
We present numerical results of the mutual coupling between photonic crystal cavities and semiconductor quantum dots. Normal mode splitting between a single cavity mode and a single quantum dot is shown under weak excitation, while under strong excitation Q‐factor dependent side bands appear, according to the AC‐Stark effect. Coupled photonic crystals, aligned parallel but displaced under a 30°‐angle for efficient coupling, show line splittings of all eigenmodes, if a single eigenmode is resonantly coupled to a single quantum dot. The mutual coupling of N resonant quantum dots to a single cavity mode results in a N−−√ scaling of the splitting, known from quantum optics, but corrected by the field amplitude fraction for not collocated quantum dots.
Keywords: tet_topic_phc; tet_topic_qd

Wavelet‐Based Adaptive Computations of the Excitonic Eigenstates of Disordered Semiconductor Quantum Wires - Meier, Torsten; Mollet, Christian; Kunoth, Angela (AIP Conference Proceedings)
A novel adaptive wavelet based method is presented that allows us to compute eigenvalues and eigenvectors of the electronic Schrödinger equation. Our method outperforms direct discretization methods with equidistant grid spacings, in particular, for problems that involve several length scales. As an application we present numerical evaluations of the energetically lowest exciton states for ordered and disordered semiconductor quantum wires.

Theoretical approach to the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (CLEO:2011 - Laser Applications to Photonic Applications)
We present an ab-initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with sub-wavelength thickness. We find a strong localization of the second-harmonic current at the metal-vacuum interface.
Keywords: tet_topic_shg

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Key Engineering Materials)
This article will highlight various aspects of the production process of high performance active elements made of ultra high-strength steels. Focus is put on the processing of thick sheet metal regarding hot forming by means of punching, embossing, and forging processes as well as on thermo-mechanical treatment. Due to the material thickness of the semi-finished parts/blanks used and owing to the high strength of the materials (Rm > 2600 MPa) current production techniques and parameters from the field of thin sheet metal can only be limitedly be transferred and have therefore been specially investigated for this application.

Presshärten von Rohren und Profilen mittels formlos fester Stoffe - Mennecart, Thomas; Rostek, Tim; Witulski, Jörg; Brosius, Alexander; Takkaya, A. Erman; Homberg, Werner

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Proceedings. of the 10th International Conference on Technology of Plasticity (ICTP))

Teaching & Learning Guide for: New Media, Web 2.0 and Surveillance - Fuchs, Christian (Sociology Compass)

New Media, Web 2.0 and Surveillance - Fuchs, Christian (Sociology Compass)

Preface - Fuchs, Christian (İletişimi anlamak (Understanding communication), 4th revised)